Peran Jurnalis Terhadap Perkembangan Olahraga Pariwisata Sumatera Barat - Rino Warisman Putra; Muhamad Sazeli Rifki; Nugroho Susanto; Sonya Nelson (Lembaga Pengembangan Kinerja Dosen, 2024)
The problem in this study is seen from the lack of participation and activeness of journalists in reporting tourism sports events in West Sumatra, this has an impact on public knowledge in recognizing what types of tourism sports are, considering that West Sumatra has a very supportive landscape for holding tourism sports events. The type of research is qualitative research. Qualitative research will produce descriptive data in the form of interview results with relevant sources narrated in the research results. With a qualitative approach, it is expected to reveal comprehensive facts about the role of journalists in the development of sports tourism in West Sumatra. The research was conducted in three news agencies, namely Langgam.id, Klikpositif.com, and Harian Singgalang. The research findings revealed the lack of journalist participation in the development of West Sumatra sports tourism due to the lack of socialization by event organizers to journalist. Meanwhile, the role of journalists in the development of sports tourism in West Sumatra is as a disseminator of actual and in-depth information to the public about sports and tourism.